Księgozbiór parafii we Wrzawach w świetle wizytacji generalnej z 1748 roku - Moskal, Tomasz (Saeculum Christianum. Pismo Historyczne, 2019)
The article presents the parish library in Wrzawy in 1748. Information about it was provided by the protocol of the general visitation of the archdeaconry of Zawichost in the diocese of Cracow, realized by the archdeacon of that time, Józef Cyprian Lange (+1757). The collection of 15 books had a typically pastoral character. Texts of the Holy Scriptures, homiletic works of Alexander Lorencowicz, Sebastian Stryjewicz, Jan Osorius, Didacus Nisenus theological-moral Jan Busaeus, Robert Bellarmine, Ludwik of Granada and ascetic Tomasz and Kempis, helped to work on the pulpit or in the confessional. Thus, although it was not a collection of books, it was varied in content.